Mapping the South China Sea Conflict through the Dynamic Framework Theory on Conflict Prevention and Peacebuilding - Budi Setiawan; Bayu Setiawan; Eri Hidayat (Formosa Journal of Social Sciences (FJSS), 2024)
he dynamics of the South China Sea conflict hold the potential for certain levels of escalation. The complexity of the conflict in the South China Sea needs to be specifically unraveled through the theory of the dynamic framework for conflict prevention and peace. This involves identifying the components that trigger and drive the conflict, which can then serve as a reference for formulating measures to prevent the escalation of the conflict. In this study, the South China Sea conflict is the primary object of exploration using the dynamic framework theory for conflict identification. The dynamic conflict framework has interrelated components that can be synthesized to determine that the South China Sea conflict is in a critical situation